Animated learning on "Environment is our friend" Topic in Social Science Subject - Ni Wayan Yuna Kharismayani; I Gde Wawan Sudatha; I Gusti Ayu Tri Agustiana (International Journal of Elementary Education, 2022)
The lack of learning media has an impact on students' low motivation and learning outcomes. This study aims to develop a learning animation product on the social studies content for the Environmental Materials of Our Friends. This type of research is development research using the ADDIE model. The test subjects are 1 learning material expert, 1 learning media expert, and 1 learning design expert. The experiment subjects were fifth-grade elementary school students collected 30 students. Methods of data collection using a questionnaire. The data collection instrument used a questionnaire. The data analysis technique used in this research is descriptive qualitative statistical analysis and quantitative descriptive statistical analysis. The study results are the results of the assessment given by learning material experts, namely 98% (very good). The assessment given by learning media experts is 90% (very good). The assessment given by the learning design is 94% (very good). The trial results get an individual score of 100% (very good). The results of the small group trial were 98% (very good). The results of the large group trial were 92% (very good). It was concluded that the learning animation on the Social Science content of the Environmental Materials of Our Friends is suitable for learning.